Assessing the risk of consuming fish from Kanyakumari (Tamil Nadu), India: An evaluative study on bioaccumulated heavy metals in different fish species using inductively coupled plasma mass spectrometry - Suryapratap Ray; Rahul Vashishth (Toxicology Reports)
Environmental pollutants which are developing an alarming situation in the contemporary world captured attention in the present research. When it comes to food safety and security concerns it becomes an important field to be studied rigorously as food contributes majorly to human and animal health. The pollution of aquatic ecosystems by heavy metals (HMs) ultimately results in adverse effect on the food chain, which is covered in the current study. Fish is considered to be one of the main components of a balanced diet plate due to its high-quality protein, which sets it apart from other dietary sources. On the other hand, it is also susceptible to the absorption and bioaccumulation of HMs at toxic levels. In our study, we have considered three different species (Nemipterus japonicus, Oreochromis mossambicus, and Lates calcarifer) of fish collected from Kanyakumari, Tamil Nadu (India). Three organs namely liver, gill, and muscle were taken into consideration for the HM profiling using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The Arsenic (As), Cadmium (Cd), Chromium (Cr), Mercury (Hg) and Lead (Pb) were found to be in varied concentrations ranging from 0.1 to 1.13, 0.89–1.45, 9.95–30.66, 0.14–1.62, and 24.69–189.5 µg/kg respectively, in the studied organs of fish. Carcinogenic and noncarcinogenic risk assessments were also done indicating a notable level of Pb and Cr in selected fish species. The Hazard Index (HI) for Oreochromis mossambicus was >1 for adults and children, indicating future possibility of probable health hazards on daily consumption of these fish. In Oreochromis mossambicus, the cancer risk (CR) values for Cr and As were significantly high, particularly for children, indicating a possible occurrence of acute health risk as it exceeded the threshold of 1 × 10−3 and suggesting a significant concern. Though consumption of fish on daily basis in such significant quantity is practically impossible both for adult and children, rendering these species safe.